2018
DOI: 10.1002/jor.24015
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional mapping of the joint space for the diagnosis of knee osteoarthritis based on high resolution computed tomography: Comparison with radiographic, outerbridge, and meniscal classifications

Abstract: One of the most important characteristic of knee osteoarthritis (OA) is the joint space (JS) width narrowing. Measurements are usually performed on two dimensional (2D) X‐rays. We propose and validate a new method to assess the 3D joint space at the medial knee compartment using high resolution peripheral computed tomography images. A semi‐automated method was developed to obtain a distance 3D map between femur an tibia with the following parameters: volume, minimum, maximum, mean, standard deviation, median, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…[20,21] Computerized axial tomography has very specific indications in patients with lateral knee osteoarthritis and its use is reserved for evaluating bone anatomy in surgical planning. [22,23] Treatment methods for patients with lateral knee osteoarthritis are similar to those of the rest of the compartments; however patients tolerate nonoperative treatment better than those with medial compartment involvement. [24,25]…”
Section: Pertinent Physical Examination and Imagingmentioning
confidence: 99%
“…[20,21] Computerized axial tomography has very specific indications in patients with lateral knee osteoarthritis and its use is reserved for evaluating bone anatomy in surgical planning. [22,23] Treatment methods for patients with lateral knee osteoarthritis are similar to those of the rest of the compartments; however patients tolerate nonoperative treatment better than those with medial compartment involvement. [24,25]…”
Section: Pertinent Physical Examination and Imagingmentioning
confidence: 99%
“…Phase-contrast μCT is an emerging imaging technique, which is able to resolve 3D micro-scale structures in tissue samples without the need for staining or sectioning but also complements conventional histology providing additional information on the fine structure of meniscal tissues. 3D-mapping of the joint space for the diagnosis of knee OA using high resolution computed tomography has compared radiographic, normal and degenerate meniscal pathology [31]. Bioluminescence and second harmonic generation imaging reveal dynamic changes in the inflammatory and collagen landscape in early OA [32].…”
Section: Studies On Meniscal Tissues In Health and Diseasementioning
confidence: 99%
“…Many reviews have emphasized the great potential of MSCs for meniscal repair applications [25,31,36,40,42,43,45,71]. MSCs have been employed in numerous strategies aimed to promote repair of meniscal lacerations [23] and defects in the avascular inner meniscal zone [39,89,90,91] or in meniscal replacement in meniscectomised animals [83].…”
Section: Current Approaches In Meniscal Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The main gross morphologic characteristics are narrowing of the joint space width, sclerosis of the subchondral bone, and the presence of osteophytes. 2 Epidemiological and genetic studies of OA showed that many pre-OA disease statuses can be improved. 3 However, early diagnosis and treatment of OA is still a challenge due to the complexity and length of the disease process that is influenced by mechanical, biological, and structural factors.…”
Section: Introductionmentioning
confidence: 99%